Pemanfaatan Kartu kata Bergambar Untuk Meningkatkan Penggunaan Kosakata Didik. Studi Kasus Degree of Comparison - Kurniawan, Agung; La Sunra, La Sunra; Hardiyanti, Hardiyanti (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. The aim of this research is to examine the improvement of students' common vocabulary usage using flashcards as a media tool in the topic of Degrees of Comparison. The type of research conducted was Classroom Action Research, which utilized data from pre-tests, cycle reflections, and post-tests to observe the development of students during the learning process. The data collected from the pre-tests, cycle reflections, and post-tests were analyzed by calculating the average scores and grouping them into several categories. The findings of this research, which involved the use of flashcards in the topic of Degrees of Comparison, revealed an improvement in students' scores. Initially, 60% of the students were categorized as low (Very Low and Low). However, after the post-test data was collected at the end of cycle 2, none of the students fell into the low category but had moved up to the 'Intermediate' category Keywords: Kosakata sehari-hari, Flashcard, Degree of Comparison